Edge-on backscattering enhancement based on quasi-superdirective reradiation - Shen, Zhongxiang (2015)
A concept based on superdirective reradiation is presented for the sake of backscattering enhancement of a thin conducting plate at edge-on incidence. A passive structure consisting of a thin plate loaded with two conducting posts is proposed to demonstrate the concept. Through properly choosing the heights of two posts and the spacing between them, it is observed that the induced surface currents on the two loaded posts are almost 180º out of phase. An obvious enhancement of backscattering can then be obtained as a result of the quasi-superdirective reradiation produced by induced currents on the two loaded posts with each post height shorter than a quarter-wavelength. The induced current distribution is explained by virtue of the image method. Relatively small dimensions of the loaded posts make the design concept appropriate to the backscattering enhancement for airborne applications. The agreement between simulated and measured results validates our design.